Yoga module for heart disease - Shukla Isha; Sudheer Deshpande; Tikhe Sham Ganpat; Hongasandra Ramarao Nagendra (Wolters Kluwer Medknow Publications, 2015)
Background: Heart disease (HD) is the major cause of early morbidity and mortality in most developed countries. Secondary prevention aims to prevent repeat cardiac events and death in people with established HD. Lifestyle modifications play an important role in secondary prevention. Yoga has been regarded as a kind of physical activity as well as stress management strategy. Growing evidence suggests the beneficial effects of yoga on various ailments. The aim was to develop a validated Integrated Yoga Module (IYM) for HD. Materials and Methods: The content validity of IYM for HD was assessed by a panel of 40 yoga experts. The IYM protocol was developed in the form of a tailor-made yoga practices that were supported by classical texts and research evidence. Each item in the questionnaire was discussed and rated as (i) not essential, (ii) useful, but not essential, (iii) essential and the content validity ratio (CVR) was calculated using the formula developed by Lawshe. Results: The data analysis showed that out of 39 IYM practices, 32 indicated significant content validity (cut off value 0.29 as calculated by applying Lawshe's formula for CVR). Conclusion: The IYM for HD suggests good validation for managing HD. Clinical trials are needed before any recommendation can be made.